Exploring Linked Data For The Automatic Enrichment of Historical Archives - PANDIT, HARSHVARDHAN JITENDRA; Munnelly, Gary; Lawless, Seamus (My University, 2018)
With the increasing scale of online cultural heritage collections, the efforts of manually adding annotations to their contents become a challenging and costly endeavour. Entity Linking is a process used to automatically apply such annotations to a text based collection, where the quality and coverage of the linking process is highly dependent on the knowledge base that informs it. In this paper, we present our ongoing efforts to annotate a corpus of 17th century Irish witness statements using Entity Linking methods that utilise Semantic Web techniques. We discuss problems faced in this process and attempts to remedy them.
Third International Workshop on Semantic Web for Cultural Heritage (SW4CH). Co-located with 15th European Semantic Web Conference (ESWC)
Keywords: Entity linking; Ontology creation; Automatic enrichment